2009
DOI: 10.1094/ats-2009-0710-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulfosulfuron on ‘Penncross’ Creeping Bentgrass Seedlings when Applied Before or After Seeding

Abstract: Sulfosulfuron is labeled for roughstalk bluegrass (Poa trivialis L.) control in creeping bentgrass (Agrotis stolonifera L.) fairways. Between or following applications, managers often overseed creeping bentgrass to repopulate bare or thin areas left by dying roughstalk bluegrass. Our objective was to establish safe application intervals for sulfosulfuron before or after seeding creeping bentgrass. Treatments were arranged in a 3 × 8 factorial with three sulfosulfuron application rates (13, 26, or 52 g ai/ha) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Ethofumesate is recommended to be applied no earlier than 1 to 2 weeks after emergence of PRG and 8 weeks after emergence of KBG, whereas mesotrione is recommended to be applied no earlier than 4 weeks after emergence of either KBG or PRG (Syngenta Crop Protection, 2011; Bayer Environmental Science, 2012). Our results are similar to other research showing that even though herbicides applied shortly after seedling emergence may cause limited damage, cool‐season turfgrass quickly recovers with the lack of weed pressure (Sousek et al, 2014; Rutledge et al, 2009; Reicher et al, 1999, 2000).…”
Section: Evaluating Seed Ratios and Annual Bluegrass Herbicides With supporting
confidence: 91%
“…Ethofumesate is recommended to be applied no earlier than 1 to 2 weeks after emergence of PRG and 8 weeks after emergence of KBG, whereas mesotrione is recommended to be applied no earlier than 4 weeks after emergence of either KBG or PRG (Syngenta Crop Protection, 2011; Bayer Environmental Science, 2012). Our results are similar to other research showing that even though herbicides applied shortly after seedling emergence may cause limited damage, cool‐season turfgrass quickly recovers with the lack of weed pressure (Sousek et al, 2014; Rutledge et al, 2009; Reicher et al, 1999, 2000).…”
Section: Evaluating Seed Ratios and Annual Bluegrass Herbicides With supporting
confidence: 91%
“…Bispyribac-sodium is labeled for use in turfgrass as Velocity TM (Valent U.S.A. Corp., Walnut Creek, CA) and SULFO is labeled for use in turfgrass as Certainty TM (Monsanto, St. Louis, MO). Our previous research has shown that SULFO and BYS effectively control RBG (Morton et al, 2007;Rutledge et al, 2009). For instance, BYS at 56 or 74 gÁha -1 a.i.…”
mentioning
confidence: 98%
“…resulted in 93%, 95%, and 31% control, respectively (Askew et al, 2004). Because CBG can be safely seeded within 2 to 4 weeks of either BYS or SULFO application Hart, 2005, 2006;Rutledge et al, 2009), our objectives were to determine the most effective herbicide treatments for shortand long-term RBG control and to determine if interseeding with CBG after herbicide treatments will improve long-term control of RBG and conversion to CBG.…”
mentioning
confidence: 99%
“…Sulfosulfuron application timing before seeding has shown to influence establishment of cool-season grasses. Rutledge et al (2009) noted sulfosulfuron at 13 or 26 g a.i./ha applied the day of seeding or 2 weeks before significantly reduced 'Penncross' creeping bentgrass (Agrostis stolonifera L.) establishment, but applications made three weeks before seeding were safe. It was also reported that sulfosulfuron applied at 52 g a.i./ha was not safe at any timing before seeding.…”
Section: Resultsmentioning
confidence: 99%